Treatment of coronary bifurcation lesions with drug-eluting stents: insights from the first phase of the prospective multicenter german drug-eluting stent registry - Abdel-Wahab, Mohamed S.; Hochadel, Matthias; Senges, Jochen (Journal of interventional cardiology, 2012)
Background: Controversy exists about the impact of treating bifurcations on overall outcome of coronary interventions using drug-eluting stents (DES). We sought to investigate 1-year outcome of the treatment of bifurcation lesions using DES in a large “real-world” cohort. Methods and Results: Among 5,126 patients enrolled in phase I of the multicenter German Drug-Eluting Stent Registry, 814 (16%) were treated for a bifurcation lesion. Patients with bifurcations were compared to those without bifurcations in terms of baseline characteristics, major adverse cardiac and cerebrovascular events (MACCE) and target vessel revascularization (TVR) at 1 year. Usage of sirolimus-eluting stents (SES) versus paclitaxel-eluting stents (PES) was also evaluated. In total, 1,021 and 5,189 stents were implanted in the bifurcation (1.25 stents/patient) and nonbifurcation (1.2 stents/patient) group, respectively, but 64.5% of bifurcation lesions were treated with a single stent. More complex lesion and procedural characteristics were observed in the bifurcation group. However, there was no difference in 1-year MACCE rates (a composite of death, myocardial infarction, and stroke) between the bifurcation group and nonbifurcation group (8.1% vs. 8.3%, P = 0.85). Rates of TVR (11.2% vs. 10.8%, P = 0.75) and Academic Research Consoritum-defined definite stent thrombosis (0.9% vs. 0.8%, P = 0.67) were also comparable. MACCE and TVR rates remained similar after adjustment for differences in baseline characteristics. MACCE and TVR in SES patients were 7.2% and 12.6% versus 8.7% and 10.2% in PES patients (P = 0.46 and P = 0.30, respectively). Conclusion: In this large multicenter registry, treatment of bifurcation lesions with DES appears effective and safe. The presence of bifurcations did not affect 1-year outcomes after DES implantation. The outcomes for SES and PES were similar. (J Interven Cardiol 2012;25:344-352)
Gesehen am 04.12.2018